Zapożyczenia litewskie dotyczące człowieka w gwarach polskich na Litwie. Aspekt semantyczny i etnolingwistyczny - Rutkowska, Krystyna; Sawaniewska-Mochowa, Zofia (Baltistica, 2012)
LITHUANIAN BORROWINGS CONCERNING A MAN IN LOCAL DIALECTS OF POLISH IN LITHUANIA. SEMANTIC AND ETHNOLINGUISTIC ASPECTSSummaryLithuanian borrowings from the semantic field MAN make 24% of all Lithuanian borrowings in the local dialects of Polish. Emotionalisms and expressivisms are especially numerous in the researched vocabulary and their role is to evaluate a man on the basis of his violation of the social norm and socially established canon of beauty.Among the researched forms there are lexemes common to local dialects and vernacular varieties of Polish and Lithuanian as well (e.g. kurdupel, kurdupelek ‘a short man’, Lith. kurdùpelis, kartùpelis ‘a potato, a short man’). There are also wide-spread proper names used in Polish local dialects in Lithuania, and in Belarusian and Russian local dialects as well (e.g. kurstać and prefixal formations pod-, wy- ‘to stimulate, to urge, to rouse’, Belarusian крстаць from Lith. kùrstyti ‘to stoke up the fire’, metaphorically ‘to urge somebody to do something, to incite, to instigate’). The range of such Lithuanian borrowings proves their domestication in Slavic languages / dialects and at the same time indicates their usefulness in the conceptualization of different aspects of human appearance and mentality.The described lexicon is well differentiated in a semantic sense. There are stylistically marked proper names categorizing a man from the point of view of his physicality, especially, a) differing from the norm of height and having visible body defects (e.g. kliszawy ‘bent’), b) ways of moving (tupotać / tupiniać ‘to trot’), c) neglected appearance (sutra ‘a sloppy, untidy woman’), and names related to mental sphere valorizing human beings according to the rationality of their behavior (kiemny ‘clever, prudent’, kwajszas ‘stupid, foolish’), temper and inclinations to different things, e.g. to garrulousness (plirpa ‘tattler’). The semantic field MAN contains affectonymes (giarutka ‘my dear, fem.’), nicknames utilized towards others / aliens (klaus'ik ‘Lithuanian’) and neutral lexemes, such as some names of the parts of the body (kulsza ‘thigh’, etc.). Names related to the sphere of sexuality have only expressive character (bibis / bibas ‘penis’, putia / put’ka / putiulka ‘pussy’, etc.).The strong anthropocentrism of Lithuanian borrowings in Polish local dialects is indicated by changes of meanings in relation to the initial lexeme. The basic meanings of Lithuanian borrowings are filled with secondary meanings in Polish local dialects and these additional meanings make the linguistic image of a man more detailed. The shift of stylistic registers is visible, as well as departing from the original neutral meaning of the word in the source-language to the emotionally marked meanings in the recipient-language (Lith. polysemous kerpla ‘a lush, furcate tree, bush; unwieldy thing; a clumsy man, duffer’ → dial. Polish kiarepła disdainfully ‘a clumsy man, duffer’).Why are the actual Lithuanian borrowings used by speakers of the local Polish dialects in Lithuania in order to conceptualize a man? The Lithuanian colloquial and dialectal lexis is so rich and expressive, and communicates different emotions and judgments so well that it makes a big reservoir of diversified forms and senses helping a man to put things in order in different existential situations.
Keywords: Polish; Lithuanian borrowings; loanwords; Polish dialects in Lithuania; semantics; ethnoliguistics